Religieuze en levensbeschouwelijke diversiteit in het leven en werk van geestelijk verzorgers - Berghuijs, Joantine; Liefbroer, Anke I. (Religie & Samenleving, 2017)
Spiritual caregivers often meet clients with another spiritual or religious orientation than their own, as they care for clients from a diversity of backgrounds and for clients who draw from multiple religious traditions. How do spiritual caregivers deal with religious diversity in their own lives? Do they themselves draw from more than one religious tradition? How do they function in a multireligious environment? Are they willing to provide interfaith spiritual care and do they see themselves as able to do so? What challenges do they see for the future? A survey was conducted among spiritual caregivers in healthcare settings, the military and penitentiary institutions in the Netherlands (n=208) to answer these questions. Implications of the results for the future of spiritual care are discussed.